A cluster randomised control trial of a multi-component weight management programme for adults with intellectual disabilities and obesity. Issue 3 (23rd August 2017) - Harris, Leanne; Hankey, Catherine; Jones, Nathalie; Pert, Carol; Murray, Heather; Tobin, Janet; Boyle, Susan; Melville, Craig
Abstract: There have been few published controlled studies of multi-component weight management programmes that include an energy deficit diet (EDD), for adults with intellectual disabilities and obesity. The objective of this study was to conduct a single-blind, cluster randomised controlled trial comparing a multi-component weight management programme to a health education programme. Participants were randomised to either TAKE 5, which included an EDD or Waist Winners Too (WWToo), based on health education principles. Outcomes measured at baseline, 6 months (after a weight loss phase) and 12 months (after a 6-month weight maintenance phase), by a researcher blinded to treatment allocation, included: weight; BMI; waist circumference; physical activity; sedentary behaviour and health-related quality of life. The recruitment strategy was effective with fifty participants successfully recruited. Both programmes were acceptable to adults with intellectual disabilities, evidenced by high retention rates (90 %). Exploratory efficacy analysis revealed that at 12 months there was a trend for more participants in TAKE 5 (50·0 %) to achieve a clinically important weight loss of 5–10 %, in comparison to WWToo (20·8 %) (OR 3·76; 95 % CI 0·92, 15·30; 0·064). This study found that a multi-component weight management programme that included an EDD, is feasible and an acceptable approach to weight loss when tailored to meet the needs of adults with intellectual disabilities and obesity.